Analisis Tingkat Keramahlingkungan Alat Tangkap Ikan Kakap Merah Berdasarkan Code of Conduct For Responsible Fisheries di Teluk Saleh - Lora Santika; Sitti Hilyana; Soraya Gigentika (LPPM Universitas Mataram, 2025)
his study aims to assess the environmental friendliness of fishing gears used in the red snapper (Lutjanus malabaricus) fishery in Saleh Bay based on the principles of the Code of Conduct for Responsible Fisheries (CCRF). Data were collected in seven villages around Saleh Bay using a snowball sampling method targeting fishers actively engaged in red snapper fishing. Data analysis followed a weighted scoring system based on nine CCRF criteria. The results show that troll line fishing gear achieved the highest score, followed by handline, set gillnet, and dropline. In contrast, speargun, bottom longline, and boat liftnet obtained lower scores. Overall, all fishing gears assessed were classified as environmentally friendly, although their performance varied across criteria. These findings indicate that the sustainability of the red snapper fishery in Saleh Bay is influenced not only by the type of fishing gear used, but also by operational practices and effective control of fishing intensity in accordance with CCRF principles.